(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
. The rapid advancement of digital technologies has significantly transformed educational systems worldwide, creating both opportunities and challenges for higher education institutions. In the digital era, students are constantly exposed to vast amounts of information originating from diverse digital sources, including online databases, social media platforms, educational technologies, and artificial intelligence systems. Consequently, the development of information culture has become an essential component of professional and personal competence. Information culture encompasses a set of knowledge, skills, values, and attitudes that enable individuals to effectively search, evaluate, process, communicate, and ethically use information.